Isochlorogenic Acid C Alleviates High-Fat Diet-Induced Hyperlipemia by Promoting Cholesterol Reverse Transport - Zheng, Liuyi; Lin, Guangyao; Li, Ruyue; Gan, Haining; Huang, Xuejun; Yao, Nan; Cai, Dake; Zhao, Ziming; Hu, Zixuan; Li, Minyi; Xu, Huazhen; Li, Leyi; et al. (Frontiers in Pharmacology, 2022)
Background: Promoting cholesterol reverse transport (RCT) has been proved to be a promising hyperlipidemia therapy since it’s more effective for the treatment of atherosclerosis (AS) caused by hyperlipidemia. Liver X receptor (LXR) agonists can accelerate RCT but most of them trigger undesirable liver steatosis due to the activation of liver LXRα. Aim: We aim to figure out whether Isochlorogenic acid C (ICAC) facilitates RCT without causing hepatic steatosis. Methods: In vitro study, we established foam macrophages and macrophages with loaded NBD-cholesterol models to investigate the competence of RCT promoting of ICAC. RT-qPCR and western Blot were used to verify ICAC’s regulation on RCT and NF-κB inflammatory pathways. In vivo study, male 6-week-old C57BL/6 mice were fed with high-fat diet (HFD) to investigate ICAC anti-hyperlipidemic effect and its functions on regulating RCT. The anti-hyperlipidemic effect of ICAC was evaluated by blood and liver lipid level, liver hematoxylin, oil red o staining, and liver coefficient. Finally, mRNA levels of genes involved in RCT and inflammation pathways in the liver and intestine were detected by RT-qPCR. Results: ICAC prevented macrophages from foaming by up-regulating of LXRα mediated RCT pathway and down-regulating expression of cholesterol absorption gene LDL-R, CD36, as well as suppressing iNOS, COX2, and IL-1β inflammatory factors. In HFD-fed mice, ICAC significantly lowered the lipid level both in serum and liver. Mechanistic studies showed that ICAC strengthened RCT pathway in liver and intestine but didn’t affect liver LXRα. Furthermore, ICAC impeded both adipogenesis and inflammatory response in liver. Conclusion: ICAC accelerated RCT without affecting liver LXRα, thus resulting in a lipid-lowering effect without increasing liver adipogenesis. Our results indicated that ICAC could be a new RCT promoter for hyperlipidemia treatment without causing liver steatosis.